The INFLUENCE OF ANDROID-BASED ROLE PLAYING LEARNING MODEL TOWARD STUDENTS’ MOTIVATION IN SPEAKING SKILL - Zailin Ayu; Ida Nuraida (FKIP, Universitas Banten Jaya, 2021)
This study aims to analyze the influence of Android-based role playing learning models towards students' motivation in speaking skills. This study used a quasi-experimental method with the Nonequivalent Control Group Design. The sample of this study consisted of two classes. The research instrument used tests and questionnaires. Based on the results of the average value of the experimental class pretest class is 59.25 and posttest is 72.95 has increased by 13.70 while the average value of the pre-test control class is 68.3 and post-test is 58.75 experienced a decrease of 9.55. The average questionnaire result data was 89.5 and it was concluded that there were differences in student motivation before and after learning with Android-based role playing models. Learning using Android-based has an influence on learning motivation of students in class X TKJ by 53% with the results of t-table > t-count (5.35 > 2.06), then the hypothesis is accepted. At the end of this study, it is hoped that learning based on Android can be used as an alternative in learning speaking skills